Association between the gut and oral microbiome with obesity. (August 2021) - Gasmi Benahmed, Asma; Gasmi, Amin; Doşa, Alexandru; Chirumbolo, Salvatore; Mujawdiya, Pavan Kumar; Aaseth, Jan; Dadar, Maryam; Bjørklund, Geir
Abstract: In recent decades, obesity has become one of the most common lifestyle-associated disorders. Obesity is a major contributing factor for several other lifestyles associated disorders such as type 2 diabetes mellitus, hypertension, and cardiovascular disease. Although genetics and lifestyle have been directly implicated in the onset and progression of obesity, recent studies have established that gut microbiome plays a crucial role in obesity progression. A higher proportion of Firmicutes and a skewed Firmicutes/Bacteroidetes ratio may contribute to gut dysbiosis and subsequent disturbances in the overall body metabolisms. Like gut microbiome, the oral cavity of humans also harbors a characteristic microbial population called "oral microbiome". The oral microbiome has also been implicated in the development of obesity due to its modulating effects on the gut microbiome. Due to its critical role in obesity, alteration in the gut microbiome has been suggested as one of the therapeutic strategies to manage obesity itself. For example, fecal microbiome transfer, or the use of probiotics and prebiotics have been suggested. These therapies not only restore the gut microbiome to the "pre-obese stage" but also ameliorate many functional aspects of the metabolic syndrome such as systemic inflammation, insulin resistance, and fat accumulation. However, the efficacy and safety of some of the methods have not been tested for their long-term implications, and further research in this area is warranted to understand the molecular mechanisms involved in this process completely. Highlights: The gut microbiota plays a crucial role in obesity progression. The oral microbiome is implicated in obesity development. This occurs due to modulation on the gut microbiota. Oral microbiota cross talks with gut microbiota. Treatment of the gut microbiota is a possible therapeutic strategy to manage obesity.